Rancangan Dan Aplikasi Sistem Keamanan Kendaraan Bermotor Menggunakan Mikrokontroler Dan GPS Modul Dengan Metode Prototyping Berbasis Android - Yonathan; Indra Cahya Firdaus (CV. Multi Kreasi Media, 2024)
Currently, the number of motor vehicle theft cases is still quite high, this happens because of the inadequate security system on vehicles produced by manufacturers, where security systems are generally limited to alarms and handlebar locks that can be outsmarted by criminals. With these security tools, vehicles that have been taken by criminals are difficult to find again. To overcome this problem, a